Sosialisasi dan Edukasi Produk Inovatif: Studi Pengembangan Karakter Kewirausahaan di SMK Negeri 1 Musuk - Lathifah Sukma Sari; Umi Safitri; Defitri Ayu Lestari; Ariyo Fajar Wibowo; Unna Ria Safitri (Lembaga Pengembangan Kinerja Dosen, 2026)
The world of education must actively participate in preparing a creative, innovative, and competitive generation in response to advances in technology and science. Schools, as formal educational institutions, have a great responsibility to improve students' entrepreneurial skills by adding innovative product development theory to the learning process. Amidst increasingly fierce competition, product innovation is essential to create added value and maintain the sustainability of managed businesses. Entrepreneurship also plays an important role in driving social change and economic growth. Students are also encouraged to learn to be more creative, take initiative, and dare to take risks if they are given the facilities to develop their entrepreneurial spirit at school. Practical learning, training in innovative product creation, and business management simulations help students understand and apply entrepreneurial principles efficiently. Schools are expected to be a sustainable place for developing students' entrepreneurial character through targeted outreach and instruction. This method not only improves students' knowledge and skills, but also builds independence and innovation, which can help students prepare for the world of work, business, and industry. The goal is to foster an entrepreneurial culture focused on developing personal potential, thereby producing independent, adaptive, highly competitive graduates who are ready to face global challenges.